Effect of Interest Rates on Banks Profitability: The Case of GCB Bank PLC - Elizabeth Sarfo-Kantanka; Oscar Opoku Agyemang; Isaac Opoku Dadzie; Verosivera Boateng; Owusu-Debrah Mark (HM Journals, 2022)
The study was to examine the impact of change of interest rate on banks profitability. Specifically, it sought to identify the relationship between the change of interest rate and banks profitability for the period 2008-2019; and to determine the effect of change of interest rate on banks profitability for the period 2008-2019. The study was an explanatory research design of quantitative approach that extracted data from the Annual Financial Reports of GCB Bank Plc on Return on Assets (ROA), Return on Equity (ROE) and Bank Size of GCB, and the Monetory Interest Rates by the Bank of Ghana from 2008 to 2019. Both descriptive statistics such as freqauencies, means and standard deviation as well as inferencial statistics such as multiple regression were used in the data analysis. Overall, this study concluded that the Change of Interest Rate (CIR) have significant effect on Banks Return on Assets (ROA) and Return on Equity (ROE), and by extension affective banks profitability. It was established that yearly interest rates of Ghana, as reported by the BoG on monthly basis have seen some fluctuation over the last 12 years. The highest positive change in percentage of 23.21 was recorded in 2015, whereas 2018 recorded the highest negative change of -20.22, and 2012 recorded no change change. Also, there was significant relationships between the Change of Interest Rate (CIR) and Banks Profitability, specifically Return on Assets (ROA), Return on Equity (ROE) and Bank Size.